Pertimbangan Mahkamah Agung Memutus Perkara dibidang Perikanan Berupa Pengoperasionalan Kapal Tanpa Surat Ijin Penangkapan Ikan (SIPI) - Lufti Abraham (Verstek, 2019)
This study aims to determine the consideration of the Supreme Court deciding on the feld of fshery in the form of the operation of the ship without the fshing license (SIPI). The research method used is normative legal research. The approach used is a case approach approach. Sources of legal materials used are primary and secondary legal materials. It is known that the consideration of the Supreme Court granted the appeal of the Public Prosecutor in the case of the operational of a ship without a fshing license (SIPI) conducted by Defendant Syaifullah alias Ipul bin Abdullah on the basis that Judex Facti has misinterpreted the Letters of Ships, Certifcate of Eligibility Sailing or one of them interpreted as Fishing Permit Permit (SIPI). The Supreme Court then annulled the Tarakan District Court Decision Number 91/Pid.Sus/2015/PN.Tra dated July 9, 2015 and adjudicated itself saying the Defendant has been proven legally and convincingly guilty of committing a criminal offense in the feld of fsheries and imposing a criminal offense against the Accused therefore with imprisonment for 6 (six) months and a fne of Rp.1.000.000.000,00 (one billion) rupiah for 3 (three) months subsidair for imprisonment. Under the aforementioned provision, the Supreme Court’s consideration is in accordance and in compliance with the provisions of Article 256 jo of Article 193 paragraph (1) of the Criminal Procedure Code.Keywords: Cassation, Judge Consideration, Crime in the Field of Fisheries